Dysfunctional Mitochondria and Mitophagy as Drivers of Alzheimer’s Disease Pathogenesis - Chakravorty, Anushka; Jetto, Cuckoo Teresa; Manjithaya, Ravi (Frontiers in Aging Neuroscience, 2019)
Abstract Neurons are highly specialized postmitotic cells that are inherently dependent on mitochondria owing to their high bioenergetic demand. Mitochondrial dysfunction is therefore associated with various age-related neurodegenerative disorders such as Alzheimer’s disease (AD), wherein accumulation of damaged and dysfunctional mitochondria has been reported as early symptoms further contributing to disease progression. In AD, impairment of mitochondrial function causes bioenergetic deficiency, intracellular calcium imbalance and oxidative stress thereby aggravating the effect of Aβ and tau pathologies, leading to synaptic dysfunction, cognitive impairment and memory loss. Although there are reports suggesting the intricate parallelism between mitochondrial dysfunction and AD pathologies such as A aggregation and hyperphosphorylated tau accumulation, the factors that drive the pathogenesis of either are unclear. In addition, emerging evidence suggests that mitochondrial quality control (QC) mechanisms such as mitophagy is impaired in AD. As an important mitochondrial QC mechanism, mitophagy plays a critical role in maintaining neuronal health and function. Studies show that different proteins involved in mitophagy, mitochondrial dynamics and mitochondrial biogenesis are affected in AD. The compromised mitophagy may also be attributed to impairment in autophagosome-lysosome fusion and defects in lysosomal acidification. Therapeutic interventions aiming to restore mitophagy functions can be used as a strategy for ameliorating AD pathogenesis. Recent evidence implicates the role of microglial activation via mitophagy induction in reducing amyloid plaque load. This review summarizes the current developments in the field of mitophagy and mitochondrial dysfunction in AD.